(untitled) (Nepal Journal of Neuroscience, 2001)
Introduction: This prospective study aimed to compare the efficacy and safety of watertight versus non-watertight duraplasty techniques in patients undergoing decompressive craniectomy (DC) for severe traumatic brain injury (TBI). Material and Methods: We evaluated 48 patients with severe TBI who underwent DC, with 24 receiving watertight duraplasty and 24 receiving non-watertight duraplasty. Primary outcomes included the incidence of cerebrospinal fluid (CSF) leaks, postoperative infections, and wound healing disturbances. Secondary outcomes included operative duration, ICU stay, hospital stay, mortality, and Glasgow Outcome Scale (GOS) scores at 6 months post-surgery. Data were compared using appropriate statistical tests, and results were benchmarked against international publications. Results: Watertight duraplasty significantly reduced the incidence of CSF leaks (8.3% vs. 29.2%, P=0.041) and shortened hospital stay (22.8 ± 6.3 days vs. 28.4 ± 7.2 days, P=0.027) compared to non-watertight duraplasty. Although the watertight group had fewer postoperative infections (12.5% vs. 25.0%) and wound healing disturbances (8.3% vs. 20.8%), these differences were not statistically significant. The operative duration was longer for the watertight group (145 ± 25 minutes vs. 115 ± 20 minutes, p<0.001). ICU stay (12.5 ± 4.2 days vs. 14.3 ± 5.1 days, P=0.187), mortality rates (8.3% vs. 12.5%, P=0.642), and GOS scores (3.5 ± 1.1 vs. 3.3 ± 1.2, P=0.483) were similar between the groups. Conclusion: Watertight duraplasty is associated with lower rates of CSF leaks and shorter hospital stays but requires longer operative times. However, the absence of significant differences in infection rates, wound healing, ICU stay, and long-term neurological outcomes indicates the need for further research. The comparison of our results with international publications underscores the global relevance of optimizing duraplasty techniques to improve patient outcomes in neurosurgery.